INNOVATIVE METHODS OF DRILLING OIL AND GAS WELLS - Mansurov Aziz Abdikarimovich (Western European Studies, 2025)
Innovative drilling technologies have transformed the global oil and gas industry during the past two decades, enabling operators to reach complex hydrocarbon reservoirs with greater accuracy, efficiency, and sustainability. Traditional rotary drilling is increasingly complemented—or replaced—by advanced techniques such as directional and horizontal drilling, multilateral well architecture, managed pressure drilling (MPD), underbalanced drilling (UBD), laser and plasma drilling, automated rig control, and digital subsurface modeling. These innovations reduce non-productive time (NPT), enhance wellbore stability, lower drilling risks, and improve recovery factors in unconventional, deepwater, and highpressure/high-temperature (HPHT) environments. The integration of Artificial Intelligence (AI), Machine Learning (ML), Internet of Things (IoT) sensors, and real-time analytics has further optimized drilling performance by enabling predictive maintenance, automated decision-making, and advanced geosteering capabilities
Keywords: Oil and gas drilling; innovative drilling technologies; horizontal drilling